2013
DOI: 10.1088/1367-2630/15/1/015020
|View full text |Cite
|
Sign up to set email alerts
|

Impact of extended preplasma on energy coupling in kilojoule energy relativistic laser interaction with cone wire targets relevant to fast ignition

Abstract: Cone-guided fast ignition laser fusion depends critically on details of the interaction of an intense laser pulse with the inside tip of a cone. Generation of relativistic electrons in the laser plasma interaction (LPI) with a gold cone and their subsequent transport into a copper wire have been studied using a kJ-class 9 Current address:

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

1
6
0

Year Published

2013
2013
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 9 publications
(7 citation statements)
references
References 36 publications
1
6
0
Order By: Relevance
“…In the last years several groups have performed PIC studies of the effect of pre-plasma on the laser absorption and particle acceleration [45,49,[81][82][83][84][85][86][87][88][89]. It has been shown that an increase in the amount of pre-plasma not only places the absorption region further way from the core, leading to a reduced number of fast electrons reaching the core due to their divergence, but it also changes the dynamics of the laser propagation and the characteristics of the laser-generated fast electrons.…”
Section: Effects Of Pre-plasmamentioning
confidence: 99%
“…In the last years several groups have performed PIC studies of the effect of pre-plasma on the laser absorption and particle acceleration [45,49,[81][82][83][84][85][86][87][88][89]. It has been shown that an increase in the amount of pre-plasma not only places the absorption region further way from the core, leading to a reduced number of fast electrons reaching the core due to their divergence, but it also changes the dynamics of the laser propagation and the characteristics of the laser-generated fast electrons.…”
Section: Effects Of Pre-plasmamentioning
confidence: 99%
“…In the last years several groups have performed PIC studies of the effect of preplasma on the laser absorption and particle acceleration [81,82,45,49,83,84,85,86,87,88,89]. It has been shown that an increase in the amount of pre-plasma not only places the absorption region further way from the core, leading to a reduced number of fast electrons reaching the core due to their divergence, but it also changes the dynamics of the laser propagation and the characteristics of the laser-generated fast electrons.…”
Section: Effects Of Pre-plasmamentioning
confidence: 99%
“…In this letter we propose a successful approach to create and to study WDM based on the use of wire targets irradiated by short-pulse high-intensity lasers. Let us notice that although wire targets have already been used in previous recent experiments, these experiments were really focusing on the aspect of fast electron propagation [33][34][35] (in particular in the "cone attached" configuration) or on the hydrodynamic evolution [36], while here we focus on the creation and investigation of WDM state.…”
mentioning
confidence: 99%